2020
DOI: 10.1099/acmi.0.000123
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Streptococcus pneumoniae serotype 6B from a patient with bacterial meningitis infection in Jakarta, Indonesia

Abstract: CNS infection is a life-threatening condition in developing countries and Streptococcus pneumoniae has been reported as the most common cause of bacterial meningitis; however, there is limited data on pneumococcal meningitis in Indonesia. This cross-sectional study aimed to isolate and identity S. pneumoniae strains from cerebrospinal fluid (CSF) specimens collected as part of routine testing from patients with clinically diagnosed central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
2
7
1
Order By: Relevance
“…In this study, ampicillin (100%), ceftriaxone (100%), chloramphenicol (77.80%), ciprofloxacin (83.30%), penicillin G (100%), vancomycin (87.50%), and erythromycin (80%) are the most effective antimicrobial agent for S. pneumoniae isolates. This finding was in agreement with studies conducted by Purwanto et al and by Gudina et al 17 , 33 However, a study by Assegu Fenta D et al 18 and Khan et al 24 reported that S. pneumoniae was resistant to ceftriaxone and penicillin. Cefoxitin (100%) and clindamycin (100%) are the most effective drugs for S. aureus isolates while erythromycin (66.80%) and amoxicillin (66.80%) are functional against S. aureus isolates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, ampicillin (100%), ceftriaxone (100%), chloramphenicol (77.80%), ciprofloxacin (83.30%), penicillin G (100%), vancomycin (87.50%), and erythromycin (80%) are the most effective antimicrobial agent for S. pneumoniae isolates. This finding was in agreement with studies conducted by Purwanto et al and by Gudina et al 17 , 33 However, a study by Assegu Fenta D et al 18 and Khan et al 24 reported that S. pneumoniae was resistant to ceftriaxone and penicillin. Cefoxitin (100%) and clindamycin (100%) are the most effective drugs for S. aureus isolates while erythromycin (66.80%) and amoxicillin (66.80%) are functional against S. aureus isolates.…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of culture-positive bacterial meningitis among adult patients in this study is 1.28%, which is higher than a study carried in Indonesia (0.68%). 17 However, it is lower than reported in Ethiopia (6.90%), 18 Malawi (5.25%), 19 South African (10.70%), 20 Kenya (11.20%), 21 Netherlands (13%), 22 Yemen (52.70%), 23 and Qatar (53.60%), 24 which differs noticeably among studies, might be due to differences in characteristics and geographical distribution of the study population, sample size, diagnostic techniques, and differences in infection control policies. We noticed a significant prevalence of bacterial meningitis among adult patients, which indicates adults remain the population where the disease meningitis prevalent and strict prevention strategies are required.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the majority of the isolated S. pneumonia were sensitive to ampicillin (100%), ceftriaxone (100%), chloramphenicol (77.8%), cipro oxacin (83.3%), penicillin G (100%), vancomycin (87.5%), and erythromycin (80%). This nding was in agreement with studies conducted by Purwanto DS et al [17] and by Gudina EK et al [33]. However, a study by Assegu Fenta D et al [18] and Khan FY et al [24] reported that S. pneumoniae was resistant to ceftriaxone and penicillin.…”
Section: Discussionsupporting
confidence: 91%
“…We performed this study to summarize prevalence gures obtained from CSF samples, with an exclusive focus on adults. The overall prevalence of bacterial meningitis among adult patients in this study is 1.28%, which is higher than a study carried in Indonesia (0.68%) [17]. However, it is lower than reported in Ethiopia (6.9%) [18], Malawi (5.25%) [19], South African (10.7%) [20], Kenya (11.2%) [21], Netherlands (13%) [22], Yemen (52.7%) [23] and Qatar (53.6%) [24], which differs noticeably among studies, might be due to differences in characteristics and geographical distribution of the study population, sample size, diagnostic techniques, and differences in infection control policies.…”
Section: Discussioncontrasting
confidence: 78%
“…Meningitis causes significant neurosensory consequences and a high fatality rate (about 117,000 deaths annually globally). The disease’s median incidence in children under five is 34 cases per 100,000 children annually [ 6 ]. The incidence varies by global region; in the Americas, it is 16.6 per 100,000 children year, whereas in Africa, it is 143.6 per 100,000 children annually.…”
Section: Introductionmentioning
confidence: 99%